On and off the ice: A case study of the involvement of parents in competitive youth hockey - Thompson, Kimberley A (University of Ottawa (Canada), 2010)
Initially played for fun, friendship, and an opportunity to exercise, hockey has since become a Canadian tradition rendering it an obsessively competitive culture year-round (Russell, 2(00). Several incidents of inappropriate parental behaviours at minor hockey games have recently received national media attention (Robidoux & Bocksnick, 2010). Hence, it is critical that parents examine their own beliefs and attitudes regarding what they believe youth sports should be all about (Heinzmann, 2002), which highlights the need for research in the area of parental involvement in youth hockey. The purpose of this case study was to investigate the involvement of parents in competitive youth hockey from a symbolic interactionist perspective. More specifically, the purpose was: (a) to explore how parents create their role within the competitive youth hockey culture, and (b) to explore how parents perceive and deal with prevailing issues of aggression within the hockey environment. The study focused on a 'Peewee AA' (11-12 years old) boys' hockey team (parents, players, coaches) registered in a minor hockey association. Within this specific team, three families were also recruited to serve as multiple cases from which in-depth accounts were portrayed. Data were collected throughout a hockey season using: direct observation, participant observation, semi-structured interviews, and in-depth interviews. Findings of this study showed that youth hockey becomes a "lifestyle", whereby the demands were remarkably comparable to that of a professional endeavour, allotting minimal time for "kids to be kids". Parents acknowledged that issues of aggression arise as competition increases, yet they somehow did not recognize themselves as complicit contributors to their existence. Rather, they projected blame on the conflicting yet prevailing beliefs embedded in the culture. While parents expected their children to behave in the manner they deemed "acceptable", much of their own observed behaviours displayed incongruence, creating a sometimes hostile environment among parents, whereby policies were neglected and responsibility for helping ensure a healthy and respectful environment was disregarded. Findings highlight the need for parents, with the support of the larger youth hockey movement, to be held accountable for their behaviours as much as they need to be responsible for sustaining this cultural creation.
Keywords: Education, Physical.; Recreation.